Dietary patterns and the effect of long-term PM2.5 exposure on metabolic syndrome among Chinese adults: a cross-sectional study - Huizhen Mao; Wen Wang; Liyong Lu; Wenzhong Huang; Yu Min; Chaohui Wang; Weibin Liao; Jay Pan; Wei Lin; Ke Ju (Environmental Research Letters, 2024)
Limited evidence exists regarding the causal effects of air pollution and metabolic syndrome (MetS), as well as the potential moderating effect of adherence to healthy dietary patterns. We recruited participants with accessible clinical characteristics, dietary patterns, and blood biomarkers data from the 2009 China Health and Nutrition Survey. Multi-biomarkers combined with physical examinations were used to determine the status of MetS. The fine particulate matter (PM _2.5 ) concentration was calculated by the near-real-time historical data at the resolution of 1 km. The control function (CF) combined with probit model (CF-Probit) was used to determine the effect of long-term PM _2.5 exposure on MetS risk, with wind speed serving as the instrument. We assessed the dietary patterns of each participant using the dietary balance index (DBI). The modification analyses were conducted to investigate the potential moderating role of dietary patterns. The study included 4,277 adult participants participated with a mean age of 50.18 years and an incidence of MetS of 22.38% (957/4277 cases). The mean score for the DBI was 40.23. The mean long-term PM _2.5 level was 65.79 μ g m ^−3 . The CF-Probit marginal effects analysis showed significant causal effects of chronic PM _2.5 exposure on MetS incidence, with a marginal effect of 0.013 (95% confidence interval (CI): 0.003–0.022), suggesting that the average partial effect of long-term PM _2.5 level on the risk of MetS in adults is 1.3 percentage points. The modification analysis indicated that the average partial effect of PM _2.5 level on the risk of MetS is higher for male compared to female (4.22 pencetage points, 95% CI: 2.12 percentage points, 6.35 percentage points) and greater associated with unhealthy dietary patterns (1 percentage point, 95% CI: 0.17 percentage points, 1.86 percentage points). This study found that long-term exposure to PM _2.5 increases the risk of MetS, while a healthy dietary pattern can modulate this effect. The findings can provide scientific basis for health protection guidelines for air pollution and provide dietary recommendations for populations.